IMPLEMENTATION OF POROUS-WALLED INFILTRATION WELL DESIGN TO REDUCE SURFACE RUNOFF AT CAMPUS I STATE UNIVERSITY OF MALANG USING EPA SWMM 5.2 SOFTWARE - Asa Faidho Rizkia Fahmi; Eko Setyawan; Vita Ayu Kusuma Dewi; Titi Rahayuningsih (Department of Civil Engineering, Faculty of Engineering, Universitas Islam Malang, 2024)
The rapid expansion of urban activities at Universitas Negeri Malang has reduced rainwater infiltration and increased surface runoff, raising flood risks. At Campus I, the limited drainage capacity necessitates a green infrastructure-based solution. This study designs an optimal porous-walled infiltration well system and determines its quantity and distribution using EPA SWMM 5.2. Unlike previous studies, this research integrates site-specific permeability data from laboratory testing into the modeling process for greater accuracy. A descriptive quantitative approach was applied, with runoff discharge estimated using the Rational Method and permeability tested via the Falling Head Permeability Test. EPA SWMM 5.2 modeling, incorporating the Low Impact Development (LID) feature, was used to analyze flooding and assess system effectiveness. The findings provide recommendations for an optimized infiltration well design, offering a precise and adaptable rainwater management solution. Keywords: Infiltration Well; Porous Wall; Surface Runoff; EPA SWMM.